Contributions of Applied Behavior Analysis (ABA) in Autism Spectrum Disorder: An integrative review (Research, Society and Development, 2024)
Applied Behavior Analysis (ABA) is an approach based on the principles of behavioral psychology. It is often used in the treatment of individuals with Autism Spectrum Disorder (ASD). In the context of ASD, ABA is utilized to teach new skills and reduce challenging behaviors. This study aims to describe the contributions of Applied Behavior Analysis in the treatment and development of psychosocial skills in individuals with Autism Spectrum Disorder. An integrative literature review from the last 10 years was conducted using the databases Science Direct, Scopus, and Web Of Science, employing controlled descriptors "Applied Behavior Analysis", "Autism Spectrum Disorder", "Behavioral Therapy", and "Behavioral Intervention", combined with the Boolean operator AND. Seventeen articles comprised this review, which show positive results for the evaluated interventions. However, it is emphasized that each individual with autism has unique needs and may respond differently to different approaches. The choice of intervention should be made in consultation with qualified professionals and take into account the specific needs, preferences, and resources of each individual. It is important to continue conducting research to develop and evaluate new interventions and improve outcomes for autistic individuals.